Pentingnya Pengembangan Kompetensi Dalam Meningkatkan Kinerja Guru Pada SDN. 071168 Laehuwa Kecamatan Alasa Talumozoi - Ernita Hulu; Syah Abadi Mendrofa; Eduar Baene; Meiman Hidayat Waruwu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
Competency is a collection of knowledge, behavior and skills that teachers must have to achieve learning and educational goals. Competence means the ability to realize something in accordance with the tasks given to someone. This research aims The aim of this research is to find out how important it is to develop competencies in SDN. 071168 Laehuwa, Alasa Talumuzoi sub-district, to find out how teachers perform at SDN. 071168 Laehuwa Alasa Talumuzoi sub-district. The research was carried out using a qualitative approach using observation, interviews and documentation methods. Based on initial observations or observations made by researchers regarding the problem of low teacher performance. In facing their work, teachers experience boredom, tension, and even stress. This causes teacher performance to be not optimal. There are subordinates who have a high work ethic, some who have a low work ethic, some who are frustrated, some who have a high work ethic, some who have high skills, some who are less skilled. There are also those who feel bored with their work, there are those who want challenging assignments. All of these are existing situations and conditions. Based on the research results, the importance of competency development in improving teacher performance at elementary school. 071168 Laehuwa, Alasa Talumuzoi sub-district is that teachers' active participation in developing knowledge, applying innovative teaching methods, developing skills, and a positive attitude in carrying out roles and functions are important keys to creating an effective learning environment and providing a positive impact on students at State Elementary School 071168 Laehuwa.